Carbon fluoride and method for preparing the same, positive electrode sheet, and battery

CN122916112APending Publication Date: 2026-10-16DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510420304.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有锂氟化碳电池C-F键多为共价键,共价键键长较短,该键断裂过程会释放较大能量,不仅导致电池开路电压较低,而且放电过程中发热量大,如果增长C-F键,则电池开路电压更高,放电过程中更多的化学能转化为电能(如图1)

Benefits of technology

本发明采用VB族金属盐作为催化剂,可以有效催化碳材料前驱体的氟化过程,利用VB族金属盐催化剂的空间位阻作用,可以使F元素与C元素稳定在键长较长能量相对更低的离子键位置,有利于得到离子键含量更高的氟化碳产物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916112A_ABST
    Figure CN122916112A_ABST
Patent Text Reader

Abstract

The application provides a carbon fluoride and a preparation method, a positive electrode sheet and a battery. Specifically, a carbon material precursor is subjected to fluorination reaction under the catalysis of a VB group metal salt and by passing a reaction gas to obtain the carbon fluoride, and the content ratio of ionic bond type C-F bonds in the C-F bonds in the carbon fluoride is not less than 80%. The carbon fluoride provided by the application has a high content ratio of ionic bond type C-F bonds, the EMF of the Li / CFx battery constructed by the carbon fluoride is higher, the amount of chemical energy converted into heat energy in the discharge process of the battery is smaller, the heat generation amount in the discharge process of the battery is reduced, and the thermal runaway problem of the lithium carbon fluoride battery is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a fluorinated carbon, its preparation method, a positive electrode sheet, and a battery. Background Technology

[0002] Fluorinated graphite (CFx) was first studied by Watanabe et al. and commercially developed by Panasonic in Japan in 1970. This compound is prepared by a combination reaction of fluorine gas and carbon at high temperatures, and the value of x varies between 0 and 1.3 depending on the fluorination temperature. The type of CF bond, directly reflected in the bond length, has a direct impact on the electrode electromotive force (EMF) of the battery. A higher proportion of ionic CF bonds results in a higher EMF for the constructed Li / CFx battery, and according to thermodynamic laws, a smaller conversion of chemical energy to thermal energy occurs during battery discharge.

[0003] In existing lithium-carbon fluoride batteries, the CF bonds are mostly covalent bonds, which are relatively short. The breaking of these bonds releases a significant amount of energy, resulting in a low open-circuit voltage and high heat generation during discharge. If the CF bond length is increased, the open-circuit voltage will be higher, and more chemical energy will be converted into electrical energy during discharge (e.g., ...). Figure 1 ). Summary of the Invention

[0004] This invention aims to at least partially solve one of the technical problems in the prior art. Therefore, one object of this invention is to provide a fluorinated carbon, a method for preparing the same, a positive electrode, and a battery.

[0005] In a first aspect, the present invention provides a fluorinated carbon in which the proportion of ionic CF bonds in the fluorinated carbon is not less than 80%, preferably 85% to 96%.

[0006] The fluorinated carbon provided by this invention has a high proportion of ionic CF bonds, resulting in a higher EMF for the constructed Li / CFx battery. At the same time, according to the thermodynamic laws, the amount of chemical energy converted into thermal energy during battery discharge is smaller, thereby reducing the heat generated during battery discharge and solving the thermal runaway problem of lithium fluorinated carbon batteries.

[0007] It should be noted that the above-mentioned proportion of ionic CF bonds is obtained by fitting the NMR test results. The content proportion of different carbon-fluorine bond types can be obtained by fitting the NMR test results (fitting peak area), such as the proportion of ionic CF bonds being 80%. The total area of ​​the fitting results is considered as 100%, and the peak area proportion of each type of carbon-fluorine bond is the content proportion.

[0008] In a second aspect, the present invention provides a method for preparing fluorinated carbon as described above, the method comprising: A carbon material precursor is fluorinated by passing a reaction gas through a group VB metal salt as a catalyst.

[0009] In the fluorination process of carbon precursors, the type of carbon precursor and the type of catalyst used in the fluorination process have a significant impact on the CF bond. The inventors discovered that using group VB metal salts as catalysts can effectively catalyze the fluorination process of carbon precursors. By utilizing the steric hindrance of group VB metal salt catalysts, the F and C elements can be stabilized at ionic bond positions with longer bond lengths and relatively lower energy, which is beneficial for obtaining fluorinated carbon products with higher ionic bond content.

[0010] In some embodiments of the present invention, the mass ratio of the carbon material precursor to the group VB metal salt is (10~10000):1, preferably (100~1000):1. For example, mass ratios of 10:1, 100:1, 500:1, 1000:1, 5000:1, 10000:1, etc., or any range between any two of the above values. Controlling the mass ratio of the carbon material precursor to the group VB metal salt within the above range can increase the content of ionic CF bonds in the fluorinated carbon.

[0011] In some embodiments of the present invention, the group VB metal salt is selected from at least one of the following: nitrate of V, chloride of V, sulfate of V, nitrate of Nb, chloride of Nb, sulfate of Nb, nitrate of Ta, chloride of Ta, and sulfate of Ta.

[0012] In some embodiments of the present invention, the carbon material precursor is selected from SP. 3 Type-structure precursor, SP 3 -SP 2 Hybrid structure precursor, SP 2 At least one of the type-structure precursors, preferably SP 3 Type-shaped precursor.

[0013] In some embodiments of the present invention, the carbon material precursor includes at least one of diamond, graphene, and activated carbon.

[0014] In some embodiments of the present invention, the reaction gas is selected from at least one of fluorine gas and hydrofluoric acid.

[0015] In some embodiments of the present invention, the temperature of the fluorination reaction is 200~400°C, and the time of the fluorination reaction is 2-48h. For example, the temperature is 200°C, 250°C, 300°C, 350°C, 400°C, etc., or any range between any two of the above values; the time is 2h, 5h, 10h, 15h, 20h, 30h, 40h, 48h, etc., or any range between any two of the above values.

[0016] In a third aspect, the present invention provides a positive electrode sheet comprising the aforementioned fluorinated carbon or fluorinated carbon obtained by the aforementioned method. Batteries prepared using this positive electrode sheet release less heat during discharge, thus solving the problem of thermal runaway during battery discharge.

[0017] In some embodiments of the present invention, a conductive agent and a binder are further included, wherein the mass ratio of the fluorinated carbon, the conductive agent and the binder is (5~10):(0.1~5):(0.1~5).

[0018] Preferably, the conductive agent includes at least one of conductive carbon black, graphene, and carbon nanotubes; Preferably, the adhesive comprises at least one of polyvinylidene fluoride, styrene-butadiene rubber, and polyurethane.

[0019] In a fourth aspect, the present invention provides a battery comprising a negative electrode, a separator, an electrolyte, and the aforementioned positive electrode. Consequently, the battery exhibits excellent electrochemical performance and low heat generation during discharge, effectively solving the thermal runaway problem of lithium fluoride batteries.

[0020] In some embodiments of the present invention, the electrolyte includes lithium salts, ester solvents, and ether solvents.

[0021] Further, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, and lithium hexafluoroarsenate. The ester solvent is selected from at least one of dimethyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, and methyl ethyl carbonate. The ether solvent is selected from at least one of ethylene glycol dimethyl ether, tetrahydrofuran, 1,2-dimethoxyethylene, 1,4-dioxocyclohexane, diethylene glycol dimethyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0022] In some embodiments of the present invention, the molar concentration of the lithium salt in the lithium fluoride carbon battery electrolyte is 0.01~10M.

[0023] In some embodiments of the present invention, the volume ratio of the ester solvent to the ether solvent is 0.01 to 100:1.

[0024] In some embodiments of the present invention, the operating temperature of the battery is -40~150°C; In some embodiments of the present invention, the allowable discharge rate of the battery during operation is 0.01C to 10C.

[0025] The present invention has at least the following technical effects: This invention uses group VB metal salts as catalysts, which can effectively catalyze the fluorination process of carbon material precursors. By utilizing the steric hindrance of group VB metal salt catalysts, the F and C elements can be stabilized at ionic bond positions with longer bond lengths and relatively lower energies, which is beneficial for obtaining fluorinated carbon products with higher ionic bond content. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0027] Figure 1 It is based on the average bond length of different types of carbon-fluorine bonds in C1s and the position of the main peak of their binding energy. Detailed Implementation

[0028] Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention. The invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the invention in any way.

[0029] Example 1 (1) This embodiment provides a lithium fluorinated carbon, and the specific preparation process is as follows: 50 gSP 3Diamond powder with a specific structure was thoroughly mixed with 0.1 g of niobium nitrate (mass ratio 500:1). The mixture was transferred to a tube furnace, and fluorine gas was introduced into the furnace at room temperature for 30 minutes at a flow rate of 50 sccm. The furnace was heated to 350°C and held for 10 hours at a heating rate of 10°C / min. The furnace was then cooled naturally while maintaining the fluorine gas flow to obtain the mixture product. This mixture product was dispersed in ultrapure water and centrifuged. Due to the significant density difference between the reactants and the product, the prepared fluorinated carbon material deposited on top of the niobium nitrate, exhibiting a clear stratification. The upper layer of fluorinated carbon product was collected. The centrifuged fluorinated carbon solution was transferred to a forced-air drying oven and dried at 80°C for 24 hours to obtain the fluorinated carbon material.

[0030] The content of ionic CF bonds in fluorinated carbon products was tested using solid-state NMR spectroscopy.

[0031] NMR results showed that ionic CF bonds accounted for 95.2% of the prepared fluorinated carbon material.

[0032] (2) This embodiment provides a lithium fluoride carbon battery, which is assembled as follows: The fluorinated carbon, conductive carbon black, and PVDF (polyvinylidene fluoride) prepared above were dissolved in N-methylpyrrolidone in a mass ratio of 8:1:1 and mixed evenly. The mixture was then coated into an electrode film with a thickness of 0.15 mm using a wet film preparation device. After vacuum drying, the film was cut into electrode sheets with a diameter of 14 mm using a slicer. The weight of the active material was then weighed and the mass of the active material was calculated. Simultaneously, using lithium foil as the negative electrode and Celgard 2500 as the separator, 70 μL of lithium fluoride battery electrolyte was added, and the cells were assembled into button cells in an argon-filled glove box. (The electrolyte preparation method is as follows: first, ethylene carbonate (EC) is fully dissolved at 50°C, then EC, ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC) are mixed in a volume ratio of 45:45:10 to prepare a 1.5 L mixture. Then, a 1 L volumetric flask is taken, 1 mol of LiPF6 is added to the volumetric flask, and the prepared mixture is added to the volumetric flask to obtain a LiPF6 electrolyte with a molar concentration of 1 mol / L.)

[0033] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 779 mAh / g and a positive electrode casing temperature of 50.1℃.

[0034] Example 2 (1) This embodiment provides a lithium fluoride carbon, and the specific preparation process differs from that of Example 1 in that: Example 2 uses SP 2 Structural graphene replaces SP in Example 1 3 Diamond powder with a structure.

[0035] NMR results showed that ionic CF bonds accounted for 90.1% of the prepared fluorinated carbon material.

[0036] (2) This embodiment provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in embodiment 1.

[0037] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 791mAh / g and a positive electrode casing temperature of 56.4℃.

[0038] Example 3 (1) This embodiment provides a lithium fluoride carbon. The specific preparation process differs from that of Example 1 in that: Example 3 uses commercial activated carbon to replace SP in Example 1. 3 The structure of the diamond powder (as determined by nuclear magnetic resonance (NMR) in this commercial activated carbon) contains SP. 2 Structural carbon and SP 3 The mass ratio of structural carbon is 1:1.

[0039] Nuclear magnetic resonance (NMR) tests showed that ionic CF bonds accounted for 90.7% of the prepared fluorinated carbon material.

[0040] (2) This embodiment provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in embodiment 1.

[0041] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 799mAh / g and a positive electrode casing temperature of 55.2℃.

[0042] Example 4 (1) This embodiment provides a lithium fluoride carbon. The specific preparation process differs from that of Example 1 in that: in Example 4, vanadium nitrate catalyst is used to replace niobium nitrate catalyst in Example 1.

[0043] NMR results showed that ionic CF bonds accounted for 89.7% of the prepared fluorinated carbon material.

[0044] (2) This embodiment provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in embodiment 1.

[0045] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 778 mAh / g and a positive electrode casing temperature of 55.3℃.

[0046] Example 5 (1) This embodiment provides a lithium fluoride carbon. The specific preparation process differs from that of Example 1 in that: in Example 5, tantalum nitrate catalyst is used instead of niobium nitrate catalyst in Example 1.

[0047] NMR results showed that ionic CF bonds accounted for 88.9% of the prepared fluorinated carbon material.

[0048] (2) This embodiment provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in embodiment 1.

[0049] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 768mAh / g and a positive electrode casing temperature of 55.5℃.

[0050] Example 6 (1) This embodiment provides a lithium fluoride carbon. The specific preparation process differs from that of Example 1 in that the amount of niobium nitrate added in Example 6 is 0.5 g.

[0051] NMR results showed that ionic CF bonds accounted for 85.3% of the prepared fluorinated carbon material.

[0052] (2) This embodiment provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in embodiment 1.

[0053] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 765mAh / g and a positive electrode casing temperature of 60.7℃.

[0054] Example 7 (1) This embodiment provides a lithium fluoride carbon. The specific preparation process differs from that of Example 1 in that the amount of niobium nitrate added in Example 7 is 0.05 g.

[0055] NMR results showed that ionic CF bonds accounted for 84.9% of the prepared fluorinated carbon material.

[0056] (2) This embodiment provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in embodiment 1.

[0057] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 754 mAh / g and a positive electrode casing temperature of 60.9℃.

[0058] Comparative Example 1 (1) This comparative example provides a lithium fluoride carbon. The specific preparation process is different from that of Example 1. Niobium nitrate is not added in Comparative Example 1.

[0059] NMR results showed that ionic CF bonds accounted for 20.3% of the prepared fluorinated carbon material.

[0060] (2) This comparative example provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in Example 1.

[0061] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 650mAh / g and a positive electrode casing temperature of 80.1℃.

[0062] Comparative Example 2 (1) This comparative example provides a lithium fluoride carbon. The specific preparation process differs from that of Example 1 in that the amount of niobium nitrate added in Comparative Example 2 is 10 g.

[0063] NMR results showed that ionic CF bonds accounted for 19.7% of the prepared fluorinated carbon material.

[0064] (2) This comparative example provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in Example 1.

[0065] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 655mAh / g and a positive electrode casing temperature of 80.4℃.

[0066] Comparative Example 3 (1) This comparative example provides a lithium fluoride carbon. The specific preparation process is different from that of Example 1. In Comparative Example 3, nickel nitrate is used to replace niobium nitrate in Example 1.

[0067] NMR results showed that ionic CF bonds accounted for 27.7% of the prepared fluorinated carbon material.

[0068] (2) This comparative example provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in Example 1.

[0069] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 659 mAh / g and a positive electrode casing temperature of 80.7℃.

[0070] Comparative Example 4 (1) This comparative example provides a lithium fluoride carbon. The specific preparation process is different from that of Example 1. In Comparative Example 4, molybdenum nitrate is used instead of niobium nitrate in Example 1.

[0071] NMR results showed that ionic CF bonds accounted for 29.4% of the prepared fluorinated carbon material.

[0072] (2) This comparative example provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in Example 1.

[0073] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 617 mAh / g and a positive electrode casing temperature of 81.1℃.

[0074] Comparative Example 5 (1) This comparative example provides a lithium fluoride carbon. The specific preparation process is different from that of Example 1. In Comparative Example 5, the fluorine gas in Example 1 is replaced with titanium fluoride powder of the same mass as diamond, and the atmosphere is replaced with argon atmosphere.

[0075] NMR results showed that ionic CF bonds accounted for 10.6% of the prepared fluorinated carbon material.

[0076] (2) This comparative example provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in Example 1.

[0077] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 660mAh / g and a positive electrode casing temperature of 81.0℃.

[0078] Comparative Example 6 (1) This comparative example provides a lithium fluorinated carbon. The specific preparation process differs from that of Example 1 as follows: In Comparative Example 6, the tubular furnace is heated to 450 degrees Celsius and kept at that temperature for 10 hours.

[0079] NMR results showed that ionic CF bonds accounted for 12.4% of the prepared fluorinated carbon material.

[0080] (2) This comparative example provides a lithium fluoride carbon battery, and the specific assembly process is the same as that in Example 1.

[0081] Electrochemical and temperature tests were performed on the assembled button batteries. The batteries were discharged at a 5C rate to 1V. A temperature sensor was attached to the center of the positive electrode side of the button battery to detect temperature changes. During the test, the specific discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded. The assembled button battery had a specific discharge capacity of 661mAh / g and a positive electrode casing temperature of 81.3℃.

[0082] In the fluorinated carbon materials prepared in Examples 1-7 of this invention, the proportion of ionic CF bonds is all above 80%, indicating a high content. The resulting batteries exhibit excellent electrochemical performance and low heat generation. In Comparative Example 1, the fluorinated carbon material prepared did not utilize the group VB metal salt catalyst of this invention. The proportion of ionic CF bonds in the fluorinated carbon material was very low, resulting in poor battery performance and high heat generation. In Comparative Example 2, the catalyst addition was too small, limiting the catalyst's effective range (atomic distance), making it impossible to fully catalyze the large-scale formation of ionic CF bonds under limited reaction conditions. Comparative Examples 3-4, using other metal salts as catalysts, failed to prepare fluorinated carbon materials with high content of long CF bonds, thus failing to achieve the goal of preparing low-heat-generating lithium fluorinated carbon batteries. In Comparative Example 5, the titanium fluoride powder could not function as a fluorinated carbon material and was difficult to separate, leading to an inability to fully resolve the battery thermal runaway problem. In Comparative Example 6, the fluorination temperature was too high, failing to obtain a large amount of ionic CF bond fluorinated carbon, further hindering the resolution of the battery thermal runaway problem.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A fluorinated carbon, characterized in that, Based on the content ratio of CF bonds in the fluorinated carbon, the proportion of ionic CF bonds is not less than 80%.

2. The fluorinated carbon according to claim 1, characterized in that, Based on the content ratio of CF bonds in the fluorinated carbon, the proportion of ionic CF bonds is 85%~96%.

3. A method for preparing fluorinated carbon as described in claim 1 or 2, characterized in that, include: A carbon material precursor is fluorinated by passing a reaction gas through a group VB metal salt as a catalyst.

4. The method according to claim 3, characterized in that, The mass ratio of the carbon material precursor to the group VB metal salt is (10~10000):1, preferably (100~1000):

1.

5. The method according to claim 3 or 4, characterized in that, The group VB metal salt is selected from at least one of the following: V nitrate, V chloride, V sulfate, Nb nitrate, Nb chloride, Nb sulfate, Ta nitrate, Ta chloride, and Ta sulfate. And / or, the carbon material precursor is selected from SP 3 Type-structure precursor, SP 3 -SP 2 Hybrid structure precursor, SP 2 At least one of the type-structure precursors, preferably SP 3 Type-shaped precursor; And / or, the carbon material precursor includes at least one of diamond, graphene, and activated carbon.

6. The method according to claim 3 or 4, characterized in that, The reactant gas is selected from at least one of fluorine gas and hydrofluoric acid; And / or, the temperature of the fluorination reaction is 200~400℃, and the time of the fluorination reaction is 2-48h.

7. A positive electrode sheet, characterized in that, This includes fluorinated carbon as described in any one of claims 1-2 or fluorinated carbon obtained by the method described in any one of claims 3-6.

8. The positive electrode sheet according to claim 7, characterized in that, It also includes a conductive agent and a binder, wherein the mass ratio of the fluorinated carbon, the conductive agent and the binder is (5~10):(0.1~5):(0.1~5); Preferably, the conductive agent includes at least one of conductive carbon black, graphene, and carbon nanotubes; Preferably, the adhesive comprises at least one of polyvinylidene fluoride, styrene-butadiene rubber, and polyurethane.

9. A battery, comprising a negative electrode, a separator, and an electrolyte, characterized in that, It also includes the positive electrode sheet as described in claim 7 or 8.

10. The battery according to claim 9, characterized in that, The battery operates at a temperature of -40 to 150°C. And / or, the allowable discharge rate of the battery during operation is 0.01C to 10C.